2023
DOI: 10.1109/tse.2023.3290237
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Engineering in the Wild: Understanding the Practitioners’ Mindset, Organizational Aspects, and Current Practices

Abstract: Privacy engineering, as an emerging field of research and practice, comprises the technical capabilities and management processes needed to implement, deploy, and operate privacy features and controls in working systems. For that, software practitioners and other stakeholders in software companies need to work cooperatively toward building privacy-preserving businesses and engineering solutions. Significant research has been done to understand the software practitioners' perceptions of information privacy, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…Case studies are shown to be one of the most common methodologies for evaluation; nonetheless, other methodologies could be considered, such as using grounded theory in the context of socio-technical systems [96]. This need for further evaluation research has also been discussed in the broader area of privacy engineering [14], [97].…”
Section: B Research Directions 1) Evaluation Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Case studies are shown to be one of the most common methodologies for evaluation; nonetheless, other methodologies could be considered, such as using grounded theory in the context of socio-technical systems [96]. This need for further evaluation research has also been discussed in the broader area of privacy engineering [14], [97].…”
Section: B Research Directions 1) Evaluation Researchmentioning
confidence: 99%
“…The scope of the validation or evaluation, as well as the methodology and techniques employed, was of particular interest. This inquiry was necessitated by prevailing criticisms, which suggest a deficiency in these methodologies, particularly in terms of their lack of a rigorous and systematic evaluation process [9], [14].…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Privacidade na Internet tem sido um assunto recorrente tanto na literatura científica quanto em literatura para o público geral, inclusive em mídias sociais online [Silva and Franc ¸a 2023]. Essa preocupac ¸ão aumentou nos últimos anos principalmente por conta de regulamentac ¸ões como a LGPD (Lei Geral de Protec ¸ão de Dados Pessoais) no Brasil e a GDPR (General Data Protection Regulation) na Europa [Iwaya et al 2023]. Outro motivo que tem aumentado as discussões em torno de privacidade na Internet é o aumento da utilizac ¸ão de técnicas de inteligência artificial, principalmente aprendizado de máquina, para classificac ¸ão de dados.…”
Section: Introduc ¸ãOunclassified